Comparison of the Pharmacokinetic Profiles of Three Low Molecular Mass Heparins – Dalteparin, Enoxaparin and Nadroparin – Administered Subcutaneously in Healthy Volunteers (Doses for Prevention of Thromboembolism) - Collignon, F; Frydman, A; Caplain, H; Ozoux, M L; Roux, Y Le; Bouthier, J; Thébault, J J (Thrombosis and Haemostasis, 1995)
The present trial was designed to comparatively investigate the pharmacokinetic profile and evaluate the apparent bioavailability pattern of three already marketed low molecular mass heparins (LMMHs): dalteparin (Fragmin®), nadroparin (Fraxiparin®), and enoxaparin (Love- nox®) given by subcutaneous route. The study was carried out in 20 healthy young volunteers given, according to a cross over design, a single subcutaneous injection of the doses recommended for the prophylaxis of deep vein thrombosis (commercial preparations, prefilled syringes): dalteparin 2,500 IU (= 2,500 IU anti-Xa), nadroparin 7,500 ICU (= 3,075 IU anti-Xa), enoxaparin 20 mg (= 2,000 IU anti-Xa) and enoxaparin 40 mg (= 4,000 IU anti-Xa). Of the markers used, activated partial thromboplastin time (APTT), thrombin clotting time (TCT), Heptest®, anti-thrombin (aIIa) activity and anti-Xa (aXa) activity, the most pertinent parameter (from a biodynamic viewpoint) is plasma aXa activity. We demonstrated that dalteparin, nadroparin and enoxaparin exhibit statistically significantly different pharmacokinetic and overall disposition patterns. Normalized to the same injected dose (1,000 IU aXa), the relative actual amount of plasma anti-Xa activity generated by enoxaparin is 1.48 times greater (p < 0.001) than that of nadroparin and 2.28 times greater (p < 0.001) than that of dalteparin while the plasma amount induced by nadroparin is 1.54 times greater (p < 0.001) than that of dalteparin. The apparent total body clearance of enoxaparin doses (CL/F = 16.7 ± 5.5 and 13.8 ± 3.2 ml/min) is significantly smaller than those of nadroparin (CL/F = 21.4 ± 7.0 ml/min ; p < 0.01) and dalteparin (CL/F = 33.3 ±11.8 ml/min ; p < 0.001) while dalteparin apparent clearance is about 1.5-fold greater (p < 0.001) than that of nadroparin. These LMMHs also differ by their renal excretion pattern : more fragments exhibiting an anti-Xa activity are recovered in urine following enoxaparin doses (6.4 and 8.7 % of the dose, respectively) than following nadroparin (3.9 %) and dalteparin (3.4 %) injection. These differences in the disposition profiles explain why the apparent elimination half life t1/2 values of the LMMHs compared here are different: dalteparin: 2.8 h; nadroparin: 3.7 h; and enoxaparin: 4.1 h. Whether or not these differences may contribute to explain the different safety/efficacy balance of each of these antithrombotic medications remains to be discussed and needs further studies.